2002
DOI: 10.1046/j.1365-2672.2002.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of Bifidobacterium adolescentis by colony hybridization as an indicator of human faecal pollution

Abstract: Aims: To develop an improved method for the detection of Bi®dobacterium adolescentis as an indicator of human faecal pollution. Methods and Results: Bi®dobacterium medium (BFM) was identi®ed as the optimal medium for the recovery of bi®dobacteria from human ef¯uent. Dilutions of faeces and ef¯uent from both humans and animals were ®ltered, grown on BFM and human speci®c B. adolescentis identi®ed via colony hybridization with a digoxigenin (DIG)-labelled oligonucleotide probe. Conclusions: The combination of BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
2
32
0
2
Order By: Relevance
“…Consequently, the specific association of B. adolescentis and B. dentium with human sewage could be used to identify the origin of fecal pollution in water. This result agrees with independent studies by different authors who proposed B. adolescentis (17) and B. dentium (23) as human-specific species. Both studies suggested these species for distinguishing human fecal pollution, although some false positives were observed in certain cases (17).…”
supporting
confidence: 93%
“…Consequently, the specific association of B. adolescentis and B. dentium with human sewage could be used to identify the origin of fecal pollution in water. This result agrees with independent studies by different authors who proposed B. adolescentis (17) and B. dentium (23) as human-specific species. Both studies suggested these species for distinguishing human fecal pollution, although some false positives were observed in certain cases (17).…”
supporting
confidence: 93%
“…Previous research has proposed that the genus Bifidobacterium be used to indicate the origin of fecal pollution (14,15). This genus fulfills most of the requirements for being a fecal indicator.…”
Section: Discussionmentioning
confidence: 99%
“…PCRbased detection and quantification methods using species-specific 16S rRNA gene-based primers are gradually becoming common in the identification of bifidobacteria. Several papers have described molecular methods for the identification of bifidobacterial isolates from selective plates (14,17,18). However, those approaches do not eliminate concerns about bias caused by inefficient recovery when culture-based methods are used.…”
Section: Bifidobacterial Quantification By Gc-16smentioning
confidence: 99%